A Comparative Study Of Motor Block And Duration Of Analgesiabetween Epidural Bupivacaine With Low Dose Butorphanol And Epidural Bupivacaine Alone In Patients Undergoing Elective Infra Umbilical Surgeries (International Journal of Food and Nutritional Sciences, 2022)
Background: The international organization for the study of pain defines pain as an unpleasant sensory and emotional experience linked to actual or potential tissue damage, or expressed in terms of such harm.Aim and Objective: The present research was aimed to compare the duration of Sensory block Motor block and analgesia between epidural bupivacaine with low dose butorphanol and epidural bupivacaine alone in patients undergoing elective infra umbilical surgeriesMethodology: This prospective, randomized clinical trial was carried out between the years of 2018 and 2020 at Santosh Medical College & Hospital in Ghaziabad, Uttar Pradesh, with approval from the Board of Studies and Ethical Committee. The whole sample included 60 ASA grade I/II patients.Result: The study population consisted of 76.7% males and 23.3% females. The mean age of the study population consisted was 39.26±10.82 years among Group Bupivacaine and 36.44±10.19 years among Group Bupivacaine + Butorphanol. The mean duration of sensory block and motor block and Analgesia was significantly more among Group Bupivacaine + Butorphanol when compared to Group Bupivacaine.Conclusion: The study concluded that bupivacaine with low dose butorphanol provided better anaesthetic properties and post operative analgesia when compared to bupivacaine alone.